Adaptação parental e percepção da autonomia do filho com autismo: relação com váriaveis sociodemográficas, abordagem clínica e inserção escolar - Santos, Tamires Dias dos (2019)
This research arose from the clinical listening of the parents of children with autism, arousing the interest in knowing how happens the psychological process of the parents of adaptation to the deficiency of the child. The birth of a child leads to family changes, but when the child has a disability, these changes tend to be more intense. The objectives of this research were to analyze the parental adaptation to the child's disability and its relation with the sociodemographic variables, as well as to describe the parents' perception about the autonomy of the child in the communication, daily life activities and motor capacity and the possible relations with the type and time of intervention. Also, evaluate the parental adaptation in relation to the type of therapy of the children and access of the parents to the psychological care. Thus, quantitative field research had a sample of 40 parents (parents and / or mothers) from 31 children diagnosed with Autism Spectrum Disorder, aged between 3 and 10 years. Two instruments were used: a semi structured interview and the Parental Adaptive Disability Scale (EPAD). From the mean of the EPAD total score, it can be seen that the parents of this research are well adapted to the child's disability; that mothers have lower adjustment scores than the fathers. When comparing the total EPAD scores of single and divorced parents, there was a significant difference, suggesting that divorced parents are better adapted than single parents. The use of antidepressants, indicating a depressive process of some parents, was associated with lower total scores in the EPAD, evidencing parents less adapted to the deficiency of the child. In relation to children, it was noticed that most of them are boys and that the autonomy of daily life is better when they attend school. Regarding the type of therapy that the child and the parents receive, it was possible to observe that the parents who participated in the therapy of the child had less feelings of guilt in relation to those who did not participate. This suggests that some parents' feelings can be worked on during the care of the children. It also demonstrates the importance of intervening with the child and the family so that parents can better adapt to disability, minimize their suffering, and help in establishing a better attachment between parents and children. The results indicated that parental adaptation follows an individual course for each parent, and that the relatives of children with ASD are not receiving psychological support for this process in the institutions investigated in Santa Maria and region.